2011
DOI: 10.1007/s00128-011-0350-8
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Zinc, Copper, Lead and Cadmium Accumulation in the Tissues of Sander lucioperca (L., 1758) Living in Hirfanlı Dam Lake, Turkey

Abstract: This study, some metals (zinc, copper, lead and cadmium) were analyzed in liver, muscle and gills of Sander lucioperca (Linnaeus, 1758) caught from the Hirfanlı Dam Lake in December 2007. The highest concentrations were found in liver (zinc:32.5 μg/g, lead:10.73 μg/g, copper:5.85 μg/g, cadmium:0.76 μg/g) of Sander lucioperca. It was seen that the accumulation of zinc, lead and cadmium primarily took place in liver followed by muscles and gills. It was observed that copper is mainly accumulated in liver followe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
6
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 11 publications
3
6
1
Order By: Relevance
“…The Cd concentration was higher in the liver than in the muscle which generally agrees with the literature (Jirsa et al 2008;Uysal et al 2009;Wang et al 2010;Gül et al 2011). The levels found in this study compared quite well with those reported elsewhere (Mendil et al 2005(Mendil et al , 2010Njogu et al 2011;Otachi et al 2014) from different freshwater fish species.…”
Section: Elementsupporting
confidence: 81%
“…The Cd concentration was higher in the liver than in the muscle which generally agrees with the literature (Jirsa et al 2008;Uysal et al 2009;Wang et al 2010;Gül et al 2011). The levels found in this study compared quite well with those reported elsewhere (Mendil et al 2005(Mendil et al , 2010Njogu et al 2011;Otachi et al 2014) from different freshwater fish species.…”
Section: Elementsupporting
confidence: 81%
“…Concentrations of Pb in freshwater fish species (Table 1) were similar to those measured in other studies (Matašin et al 2011;Gül et al, 2011;Noël et al, 2013). Sample of Giant Pangasius from Vietnam contain Pb concentration above maximum levels.…”
Section: Discussionsupporting
confidence: 86%
“…The highest element concentrations are accumulated in metabolically active tissues such as liver and gills, while muscles commonly have lower element concentrations. Such a pattern has been observed in a number of other studies covering a wide spectrum of fish species [3,7,25,[32][33][34][35][36][37][38][39][40].…”
Section: Resultssupporting
confidence: 62%